Entrepreneurial characteristics and entrepreneurial intentions among undergraduates: Case of UiTM's students - Amir, Abdul Razak; Abdullah, Syahrina; Mohamad, Armanurah (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
It is widely recognized that the entrepreneurship field was an engine of economics growth and development. For many years, entrepreneurial characteristics had been studied and research performed by many researchers. However, all those studies have not distinctively identified potential entrepreneur to be involved in an entrepreneurial training program. In this study, the researchers randomly selected respondent's students from UiTM. They are graduating undergraduates who had voluntarily attended the Undergraduates Basic Entrepreneurship Course (UBEC). UBEC is an undergraduate entrepreneurship-training program specifically allocated for graduating students. The National Entrepreneurship Institute (INSKEN) sponsors this program. The Malaysian Entrepreneurial Development Center (MEDEC) with the consent and cooperation from UiTM organizes this program. The study is to determine the relationship behveen the internal locus of control, risk taking propensity, self-efficacy and need for achievement characteristics towards entrepreneurial intentions among participants of UBEC.